Broad geographic sampling and DNA barcoding do not support the presence of Helobdella stagnalis (Linnaeus, 1758) (Clitellata: Glossiphoniidae) in North America - Iwama, Rafael Eiji; Oceguera-Figueroa, Alejandro; de Carle, Danielle; Manglicmot, Claire; Erséus, Christer; Miles, Na’ta’ne Morning-Song; Siddall, Mark E.; Kvist, Sebastian (Zootaxa, 2019)
The description of Helobdella stagnalis (Linnaeus, 1758) has emphasized the presence of a nuchal, chitinous scute located on the dorsal surface in the first third of the body as the diagnostic character for the species. Historically, identifications of species of Helobdella have relied heavily on this character and, as a result, Helobdella stagnalis has been reported from an inordinately broad geographic range, including Europe, Asia, Africa, North America, and South America. In addition to a few earlier investigations, a recent analysis showed that great genetic distances (orders of magnitude greater than previous estimations of intraspecific divergence in leeches) are present between scute-bearing specimens identified as H. stagnalis from Europe and North America, implying that H. stagnalis does not occur in North America. The present study expands the geographic boundaries of taxon sampling for both European and North American taxa, and re-examines the phylogenetic relationships and cytochrome c oxidase subunit I (COI) variation within scute-bearing species of the genus Helobdella. Our analyses include specimens putatively identified as “Helobdella stagnalis” from Sweden, Norway, Iceland, England, France, Italy, Slovenia, Turkey, Russia, and Iran, as well as numerous localities covering Canada and the USA. Our results corroborate previous studies in that European and west Asian specimens form a clade, including the neotype, which is separate from North American taxa. To alleviate future taxonomic confusion, we redescribe H. stagnalis and designate a neotype from the inferred type locality. The designation of a neotype stabilizes the taxonomy of scute-bearing leeches of the genus Helobdella and enables us to definitively correct erroneous identifications reported in previous studies. We also note that at least four lineages of scute-bearing, North American species of Helobdella lack formal descriptions.